2007
DOI: 10.1167/7.11.4
|View full text |Cite
|
Sign up to set email alerts
|

The stability of steady state accommodation in human infants

Abstract: Retinal image quality in infants is largely determined by the accuracy and the stability of their accommodative responses. Although the accuracy of infants' accommodation has been investigated previously, little is known about the stability of their responses. We performed two experiments that characterized the stability of infants' steady state accommodation. Analyses were performed in the time domain (root mean square [RMS] deviation) and in the frequency domain (spectral analysis). In Experiment 1, accommod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 71 publications
3
46
2
Order By: Relevance
“…All accommodative microfluctuation measurements decreased with advancing age in this sample of children. In addition, the mean power values for the high-frequency component (0.005 D 2 /Hz), low-frequency component (0.042 D 2 /Hz), and root mean square (0.49 D) in this study are smaller than those found by Candy and Bharadwaj25 in infants but larger than those found by Day et al12 in young adults. The accommodative ability of children in this study was not yet adult-like but more advanced than the infant state.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…All accommodative microfluctuation measurements decreased with advancing age in this sample of children. In addition, the mean power values for the high-frequency component (0.005 D 2 /Hz), low-frequency component (0.042 D 2 /Hz), and root mean square (0.49 D) in this study are smaller than those found by Candy and Bharadwaj25 in infants but larger than those found by Day et al12 in young adults. The accommodative ability of children in this study was not yet adult-like but more advanced than the infant state.…”
Section: Discussioncontrasting
confidence: 75%
“…Monocular accommodative response for measurements of microfluctuations was measured using a PowerRefractor (MultiChannelSystems, Reutlingen, Germany) at a sampling rate of 25 Hz and a test distance of 1 m. The instrument has a range of −8.75 to +4.00 D22 and requires a pupil size larger than 3.7 mm 23. Its use has been established for measuring refractive error in children24 and for the measurement of accommodative microfluctuations 11,25. While positioned in a head and chin rest to minimize the head movement, subjects viewed a high-contrast Maltese cross target (angular subtense: 1.4°) at a distance of 0.25 m (−4.00 D) continuously for two, 30-second periods while measurements were taken.…”
Section: Methodsmentioning
confidence: 99%
“…For vergence, plotted in Figure 4, the mean amplitudes were 0.068 MA for adults and 0.071 MA for infants, which were not significantly different from each other ( t = −0.11, p = 0.54). For accommodation, plotted in Figure 7, the mean amplitudes were 0.05 D for adults and 0.45 D for infants, which were significantly different from each other ( t = 2.76, p = 0.008; Candy & Bharadwaj, 2007). …”
Section: Resultsmentioning
confidence: 82%
“…[41][42][43][44] Subjects were aligned at 1 m from a set of light-emitting diodes (LEDs) immediately beneath a camera aperture. Light from the LEDs passed into the eye and was reflected back from the retina through the pupil.…”
Section: Methodsmentioning
confidence: 99%
“…The slopes of the functions were determined using linear regression, and these slopes were used to scale each participant's raw data. 32,43,47 The default PR calibration was used for subjects who did not complete that part of the data collection. Calibration slopes of individual subjects are approximately evenly distributed about the default PR calibration slope values, 46 with no strong age-related trends.…”
Section: Methodsmentioning
confidence: 99%